ANALISIS KEABSAHAN DAN EFEKTIFITAS HUKUM PELAKSANAAN RAPAT UMUM PEMEGANG SAHAM (RUPS) PERSEROAN TERBATAS YANG DILAKUKAN SECARA DARING (ONLINE) - Harry Harry; Ariawan Ariawan (Fakultas Hukum Universitas Tarumanagara, 2021)
As time goes by, of course, Science and Technology continues to develop, so that there are facilities such as internet networks and electronic media that can be used for two-way communication and allow each other to see each other such as chat, teleconference and video-conference . The implementation of the General Meeting of Stakeholders (GMS) can also be carried out by teleconference, considering the cost and time efficiency.This study aims to determine the mechanism of the general meeting of shareholders limited with online media as well as the validity of the statement on the minutes of the meeting decision general meeting of shareholders limited liability company that carried out through media teleconference by positive law in Indonesia and to review the legal effectiveness of holding general meeting of shareholders with online media